Safety of higher doses of melatonin in adults: A systematic review and meta‐analysis. Issue 2 (30th December 2021) - Menczel Schrire, Zoe; Phillips, Craig L.; Chapman, Julia L.; Duffy, Shantel L.; Wong, Grace; D'Rozario, Angela L.; Comas, Maria; Raisin, Isabelle; Saini, Bandana; Gordon, Christopher J.; McKinnon, Andrew C.; Naismith, Sharon L.; et al.
Abstract: Melatonin is commonly used for sleep and jetlag at low doses. However, there is less documentation on the safety of higher doses, which are being increasingly used for a wide variety of conditions, including more recently COVID‐19 prevention and treatment. The aim of this review was to investigate the safety of higher doses of melatonin in adults. Medline, Scopus, Embase and PsycINFO databases from inception until December 2019 with convenience searches until October 2020. Randomised controlled trials investigating high‐dose melatonin (≥10 mg) in human adults over 30 years of age were included. Two investigators independently abstracted articles using PRISMA guidelines. Risk of bias was assessed by a committee of three investigators. 79 studies were identified with a total of 3861 participants. Studies included a large range of medical conditions. The meta‐analysis was pooled data using a random effects model. The outcomes examined were the number of adverse events (AEs), serious adverse events (SAEs) and withdrawals due to AEs. A total of 29 studies (37%) made no mention of the presence or absence of AEs. Overall, only four studies met the pre‐specified low risk of bias criteria for meta‐analysis. In that small subset, melatonin did not cause a detectable increase in SAEs (Rate Ratio = 0.88 [0.52, 1.50], p = .64) or withdrawals due to AEs (0.93 [0.24, 3.56], p = .92), but did appear to increase the risk of AEs such as drowsiness, headache and dizziness (1.40 [1.15, 1.69], p < .001). Overall, there has been limited AE reporting from high‐dose melatonin studies. Based on this limited evidence, melatonin appears to have a good safety profile. Better safety reporting in future long‐term trials is needed to confirm this as our confidence limits were very wide due to the paucity of suitable data.